ANALYSIS OF INTERCONNECTION PROBLEMS DATA INDICATORS OF THE PATIENT'S QUALITY OF LIFE WITH MANUFACTURING PRINCIPLES OF REMOVABLE DENTURES - V.M. Dvornyk; H.M. Balia; K.V. Marchenko; O.V. Shemetov (Український стоматологічний альманах)
Assessing the quality of patient's life can become a crucial criterion when evaluating the effectiveness of disease treatment, as well as when comparing the efficiency of various programs: conservative and surgical treatment, various types of drug therapy, rehabilitation regimens, etc. In recent years, increasing attention has been paid to health, particularly dental, associated with the study of the life quality indicators.